CIPP Evaluation of the Implementation of the Integrated Non-Communicable Disease Development Post (Posbindu PTM) and Stakeholder Dynamics in Gatak Village - Lintang Martha Sari; Dwi Linna Suswardany (JURNAL KESMAS DAN GIZI (JKG), 2026)
Non-communicable diseases (NCDs) among adolescents show an increasing trend, necessitating promotive and preventive interventions through the Integrated Non-Communicable Disease Development Post (Posbindu PTM) for Adolescents. This study aims to evaluate the implementation of the Posbindu PTM for Adolescents in Gatak Village using the CIPP (Context, Input, Process, Product) approach. This qualitative case study design involved 17 informants from the village government, health workers, community health workers, community leaders, and active and passive adolescents. Data were collected through semi-structured interviews, observation, and documentation, and then analyzed using the Miles and Huberman interactive model.The results indicate that program planning is based on adolescent health needs and supported by cross-sector collaboration, although implementation of Primary Care Integration is not yet optimal. Resource availability is deemed adequate. The main differentiating factors between active and passive adolescents lie in peer influence and psychological readiness for health checkups. Qualitatively, the program contributed to increased knowledge and awareness of healthy lifestyle behaviors, especially among active adolescents, although the long-term quantitative impact has not been measured. The effectiveness of the program is influenced by stakeholder involvement and participatory strategies that are adaptive to the characteristics of adolescents, so that it is necessary to strengthen communication, activity innovation, and cross-sector synergy to increase the sustainability of the program.